Dramatic improvement in strength–ductility balance of dual-phase steels by optimizing features of ferrite phase - Kohei Ogatsu; Toshio Ogawa; Ta-Te Chen; Fei Sun; Yoshitaka Adachi (Journal of Materials Research and Technology)
Dramatic improvement in the strength–ductility balance of dual-phase (DP) steels by optimizing the features of the ferrite phase was attempted. Four types of specimens with and without Nb and with initial microstructures of ferrite–pearlite (P) and martensite (M) were prepared. These specimens were cold-rolled, annealed, and then water-cooled. For the specimens without Nb, the recrystallized ferrite grains in specimen M were finer and more equiaxed than those in specimen P. For the specimens with Nb, nonrecrystallized ferrite grains were observed in specimen P, whereas the finest and most equiaxed recrystallized ferrite grains were observed in specimen M. Additionally, finer recrystallized ferrite grains were formed in specimens M with Nb while maintaining equiaxiality by controlled annealing. By controlling the annealing process, the hardening of the recrystallized ferrite grains due to niobium carbide precipitation was also observed. These results indicate that fine, equiaxed, and hardened recrystallized ferrite grains can be formed by adding Nb, selecting martensite as the initial microstructure, and performing controlled annealing. The strength–ductility balance was significantly improved by adding Nb and selecting martensite as the initial microstructure. Furthermore, the strength–ductility balance of specimens M with Nb was dramatically improved via controlled annealing. This was attributed to the decrease in the strain concentration at the interface between the precipitation-strengthened ferrite and martensite in addition to the fine and equiaxed recrystallized ferrite grains. Therefore, it was concluded that the strength–ductility balance of DP steels can be dramatically improved by optimizing the features of the ferrite phase.